Relationship among Economic Growth, Internet Usage and Publication Productivity: Comparison among ASEAN and World's Best Countries - Gholizadeh, Hossein; Salehi, Hadi; Embi, Mohamed Amin; Ale Ebrahim, Nader; Danaee, Mahmoud; Motahar, Seyed Mohammad; Tanha, Farid Habibi; Osman, Noor Azuan Abu (2014)
Abstract: Publication productivity, as measured by the number of papers, has been regarded as one of the main indicators of reputation of countries and institutions. Nevertheless, the relationship among research publications, economic growth and World Wide Web in ASEAN countries is still unclear. The main intention of this study was to identify publication productivity among ASEAN and the world’s top ten countries in the last 16 years (1996-2011). This study also aimed at finding the relationship among publication, gross domestic product (GDP) and internet usage. Furthermore, the publication trend in the 10 first Malaysian universities was evaluated for the same periods. Scopus database was used to find the overall documents, overall citations, citations per document and international collaboration from 1996 to 2011 for each country. The World Bank database (World Data Bank) was used to collect the data for GDP and the number of internet users. Moreover, to evaluate 10 top Malaysian universi